Pengembangan Bahan Ajar Menggunakan Aplikasi Nearpod Berbasis Kearifan Lokal dalam Pembelajaran IPAS Sekolah Dasar - Tina Fuji Lestari; Nunu Nurfirdaus (Mataram University, 2026)
This study aimed to develop Nearpod-based teaching materials integrated with local wisdom for fourth-grade elementary science and social studies (IPAS) learning and to determine the feasibility and practicality of the developed product. The study was motivated by the limited use of interactive digital teaching materials and the lack of integration of local wisdom into classroom learning, resulting in less contextual learning experiences. Previous studies have predominantly focused on developing digital learning media without specifically integrating the local wisdom of Kuningan Regency into elementary IPAS learning, highlighting the need for more context-based teaching materials. This research employed the Research and Development (R&D) method using the ADDIE model, consisting of Analysis, Design, Development, Implementation, and Evaluation stages. The participants included one media expert, one material and language expert, one fourth-grade teacher, and 16 fourth-grade students of SD Negeri Kaduagung, Kuningan Regency. Data were collected through expert validation sheets, teacher response questionnaires, and student response questionnaires. The data were analyzed using descriptive quantitative techniques by calculating percentage scores and interpreting them according to feasibility criteria. The findings indicate that the developed Nearpod-based teaching materials achieved the very feasible category based on both media and material validation. Teacher and student responses were also categorized as very good, indicating that the product is practical for classroom implementation. The integration of local wisdom into IPAS learning successfully created more contextual and meaningful learning experiences. Therefore, the developed teaching materials are considered appropriate as an alternative digital learning resource for fourth-grade elementary school students.